(untitled) (Bangladesh Journal of Medical Science, 2023)
Leptospirosis is an endemic disease worldwide and its incidence is increasing with outbreaks and mortality. It is caused by Leptospires interrogans which are very thin, spiral-shaped, tightly coiled, gram-negative aerobic, spirochetes. It can cause several infection to human including organs such as the kidneys, liver, lungs, heart and the central nervous system. The organism can give rise to several ocular manifestations and when it affect the eyes, it causes Leptospirosisneuroretinitis. The present case illustrated a case of 9 year-old boy succumbed with leptospirosis infection presenting as neuroretinitis. The unique of the case is that the boy had noobvious systemic manifestation of leptospirosis which caused a challenge to a physician to arrive at the diagnosis. Other important differentials hadbe entertained namely toxoplasmosis and ocular tuberculosis. Further management had been discussed until the boy was discharged and being followed up as an outpatient. This is followed by the discussion on leptospirosis neuroretinitis. Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 225-228